Does Micro-Credit Empower Women : Evidence from Bangladesh - Pitt, Mark M. (World Bank, Washington, DC, 2014)
This paper examines the effects of men's and women's participation in group-based micro-credit programs on a large set of qualitative responses to questions that characterize women's autonomy and gender relations within the household. The data come from a special survey carried out in rural Bangladesh in 1998-99. The results are consistent with the view that women's participation in micro-credit programs helps to increase women's empowerment. Credit program participation leads to women taking a greater role in household decisionmaking, having greater access to financial and economic resources, having greater social networks, having greater bargaining power compared with their husbands, and having greater freedom of mobility. Female credit also tended to increase spousal communication in general about family planning and parenting concerns. The effects of male credit on women's empowerment were, at best, neutral, and at worse, decidedly negative. Male credit had a negative effect on several arenas of women's empowerment, including physical mobility, access to savings and economic resources, and power to manage some household transactions.